2006
DOI: 10.1002/bip.20476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rare earth ions on the conformational stability of anticoagulation factor II from Agkistrodon acutus venom probed by fluorescent spectroscopy

Abstract: Anticoagulation factor II (ACF II) isolated from the venom of Agkistrodon acutus is an activated coagulation factor X-binding protein in a Ca(2+)-dependent fashion with marked anticoagulant activity. The equilibrium unfolding of rare earth ions (RE(3+))-reconstituted ACF II in guanidine hydrochloride (GdnHCl) solution was studied by fluorescence. The GdnHCl-induced unfolding of RE(3+) (Nd(3+), Sm(3+), Eu(3+), Gd(3+))-reconstituted ACF II follows a three-state transition with a stable intermediate state. Substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[118][119][120][121] It has been shown that the apo-form of a metalloenzyme is more unstable than the bound form, [122,123] where the addition of native metal ions increases stability. [75,124] For example, the addition of cobalt or zinc to carbonic anhydrase refolds the molten globule state; it has been proposed that metal ions may associate with a folding intermediate to prevent aggregation pathways for this enzyme. [119,125] Furthermore, different metal ions have been shown to contribute differently to the stability of bovine carbonic anhydrase, highlighting the specificity with which metal ions contribute to stability and folding pathways.…”
Section: Instability Of Apo-enzyme States Influences the Evolvabilitymentioning
confidence: 99%
“…[118][119][120][121] It has been shown that the apo-form of a metalloenzyme is more unstable than the bound form, [122,123] where the addition of native metal ions increases stability. [75,124] For example, the addition of cobalt or zinc to carbonic anhydrase refolds the molten globule state; it has been proposed that metal ions may associate with a folding intermediate to prevent aggregation pathways for this enzyme. [119,125] Furthermore, different metal ions have been shown to contribute differently to the stability of bovine carbonic anhydrase, highlighting the specificity with which metal ions contribute to stability and folding pathways.…”
Section: Instability Of Apo-enzyme States Influences the Evolvabilitymentioning
confidence: 99%